UJI CEMARAN BAKTERI COLIFORM DAN Escherichia coli PADA AIR BERSIH SEBAGAI INDIKATOR KUALITAS LINGKUNGAN - Silmi Kafah; Indah Sulistiyawati (Bioscientiae, 2026)
Clean water plays a vital role in supporting human health and daily activities. This research aimed to analyze microbiological contamination specifically coliform and Escherichia coli bacteria in clean water as indicators of environmental quality. The study employed the membrane filter method to examine 20 water samples collected from various sources including wells, springs, and PDAM water. Microbiological tests followed the standard procedures set by the Ministry of Health Regulation No. 2 of 2023. In addition to microbiological testing, chemical parameters such as pH and iron content were also analyzed using a pH meter and UV-Vis spectrophotometer. The results indicated that not all samples met the required quality standards. Several samples contained coliform and E. coli levels exceeding the permissible limit of 0 CFU/100 mL, making them unsuitable for consumption. High bacterial levels were linked to poor sanitation practices around the water sources. The study also found that a few samples had elevated pH levels and iron concentrations, which may pose health risks. This research contributes valuable insights into water quality monitoring and underlines the importance of environmental hygiene in ensuring safe water sources.